In silico and in vivo analyses reveal key metabolic pathways enabling the fermentative utilization of glycerol in Escherichia coli. Issue 1 (26th October 2021) - Clomburg, James M.; Cintolesi, Angela; Gonzalez, Ramon
Summary: Most microorganisms can metabolize glycerol when external electron acceptors are available (i.e. under respiratory conditions). However, few can do so under fermentative conditions owing to the unique redox constraints imposed by the high degree of reduction of glycerol. Here, we utilize in silico analysis combined with in vivo genetic and biochemical approaches to investigate the fermentative metabolism of glycerol in Escherichia coli . We found that E. coli can achieve redox balance at alkaline pH by reducing protons to H2, complementing the previously reported role of 1, 2‐propanediol synthesis under acidic conditions. In this new redox balancing mode, H2 evolution is coupled to a respiratory glycerol dissimilation pathway composed of glycerol kinase (GK) and glycerol‐3‐phosphate (G3P) dehydrogenase (G3PDH). GK activates glycerol to G3P, which is further oxidized by G3PDH to generate reduced quinones that drive hydrogenase‐dependent H2 evolution. Despite the importance of the GK‐G3PDH route under alkaline conditions, we found that the NADH‐generating glycerol dissimilation pathway via glycerol dehydrogenase (GldA) and phosphoenolpyruvate (PEP)‐dependent dihydroxyacetone kinase (DHAK) was essential under both alkaline and acidic conditions. We assessed system‐wide metabolic impacts of the constraints imposed by the PEP dependency of the GldA‐DHAK route. This included the identification of enzymes and pathways that were not previously known to be involved in glycerol metabolisms such as PEP carboxykinase, PEP synthetase, multiple fructose‐1, 6‐bisphosphatases and the fructose phosphate bypass. Abstract : Hydrogen evolution and 1, 2‐PDO synthesis contribute to redox balancing during fermentative metabolism of glycerol at alkaline and acidic conditions, respectively. Involvement of different glycerol dissimilation pathways depends on the mode of redox balancing. PEP carboxykinase, PEP synthetase, multiple fructose‐1, 6‐bisphosphatases, and the fructose phosphate bypass allow the cells to cope with the stoichiometric constraints imposed by the PEP‐dependency of the essential glycerol utilization pathway, GldA‐DhaKLM.